Asuhan Keperawatan pada Keluarga Tn.K dengan Gangguan Sistem Endokrin : Diabetes Melitus di Desa Kalibuntu Rt 04 Rw 02 Kecamatan Losari Kabupaten Brebes - Dian Andini Putri; Esti Nur Janah; Siti Fatimah (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Diabetes Mellitus (DM) is a long-term metabolic disorder caused by the body's insulin hormone which cannot be used properly to regulate blood sugar balance, resulting in hyperglycemia (Zakiudin et al., 2023). There are two factors that can affect a person's glucose levels, the first is endogenous factors such as insulin, glucagon, and cortisol which act as receptor systems in liver and muscle cells. The second factor is the amount and type of food consumed, which is an exogenous factor. Blood glucose levels are also influenced by a person's character (gender, family history of diabetes, and age), dietary factors (high energy, high carbohydrates, high fat, high protein, and low fiber), lack of physical activity, nutritional status, hypertension and knowledge about nutrition (Viera Valencia & Garcia Giraldo, 2019).